Implementation of Dimer-based Screening System in Escherichia coli BL21(DE3) for Selection of Actinomycetes Compounds as Anti-HIV Candidate - Kenia Permata Sukma; Putri Cahya Destiani; Azzania Fibriani (Bogor Agricultural University, Indonesia, 2022)
Actinomycetes are reported to have inhibitory activity against several types of Human Immunodeficiency Virus proteases, enzyme with major role in the process of maturation of the virus thus it can infect new cells. Therefore, exploration of Indonesia’s actinomycetes species is expected to be a breakthrough for HIV treatment. In this study, selection of anti-HIV candidate compounds was conducted using a dimer-based screening system on recombinant Escherichia coli BL21(DE3). The construct includes the fusion of the AraC DNA binding domain + HIV-1 protease as the regulator and the green fluorescence protein as the reporter. Confirmation of the plasmid construct was carried out by PCR which showed size of 1,076 bp. Sequencing analysis proved 100% similarity and identity between construct used in this study and one previously designed. SDS-PAGE showed the presence of band in the size of 24 kDa equal to the size of the fusion protein. Compounds BLH 1-12 (2) EA, MAE 1-13 EA, BLH 1-1 EA, BLH 7-5 MetA, LC 98 (1) EA, exhibited consistent and significant protease-HIV inhibitory activity at certain concentrations. Thus, in this study, dimer-based screening system is considered to be able to detect actinomycetes as a new anti-HIV candidate for the protease inhibitor group.